Design and Development of an Interactive Scouting Educational Game Using the MDLC Approach - Achmad Buchori; Prasetio Zidan Cahya; Theodora Indriati Wardani; Nur Khoiri; Sharifah Osman (Science and Technology Research Centre Universitas PGRI Semarang, 2025)
This research aims to develop an Android-based educational game that can increase students' understanding of the concept of solving. The development method used is the Multimedia Development Life Cycle (MDLC) with a heuristic approach. This heuristic approach involves a user-oriented design process, prioritizing ease of use and compatibility with scouting materials. This game is designed with an attractive and interactive appearance, and is equipped with games that are tailored to students' abilities. The trial results show that this educational game is effective in increasing students' understanding of the concept of fractions. A part from that, students also gave positive responses to the use of games as a learning medium. This year's Scout extracurricular is indeed a non-compulsory extracurricular but schools are obliged to organize scout extracurricular activities, in the current digital era, learning media applications and educational games are really needed in schools from elementary school to high school. Therefore, this research aims to apply the basics of scouting by using articulate storyline 3 software as a learning medium for students and can be implemented during the activity.